Zawartość wybranych metali ciężkich w powierzchniowych warstwach gleb terenów zieleni uniwersyteckiej = The contents of selected heavy metals in surface layers of soils of urban green areas - Druszcz, Piotr; Pater, Oskar; Stadnik, Miłosz; Piwecka, Natalia; Cierpiński, Damian; Kołek, Arkadiusz; Malinowska, Aleksandra; Rybicka, Aleksandra; Bartyzel, Tobiasz; Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Designed green areas should be not only visually attractive, but also safe for users. The paper presents the analysis of the state of university greengrocers located on the A campus of the University of ZielonaGóra. Physical and chemical properties of soils have been tested, including the analysis of the content of total and bioavailable forms of selected heavy metals. It was found that the soil in green areas shows significant anthropogenic transformations, however the content of heavy metals does not exceed the threshold limit values.
Keywords: trawnik; zieleń miejska; zieleń niska; metale ciężkie; urban green areas; heavy metals; urban greenery